Kegiatan Penyuluhan Fisioterapi Tentang Low Back Pain Pada Kelompok Pekerja Hotel di Hotel Ascent Premiere Kota Malang - Salwa, Vasya Mutia; Rahmanto, Safun; Rakhmad Rosadi; Indah Ningtiyas Hidayanti (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2023)
Musculoskeletal disorders (MSDs) are one of the most serious health risks related to work. Industrial workers such as hotel workers are at risk of experiencing musculoskeletal disorders such as LBP. Preliminary studies conducted at the Ascent Premiere Hotel in Malang City found that workers had LBP complaints. So this counseling activity aims to provide education to hotel workers about LBP and how to do exercise therapy independently at home to reduce perceived complaints. This community service activity was carried out using a method in the form of health education regarding LBP to hotel workers using power point media and leaflets. After delivering the material, a demonstration of exercise therapy was carried out with the workers and a question and answer discussion session. This counseling activity runs smoothly and can increase the knowledge of hotel workers about LBP.